The Latar Dalam Novel ar-Rajul al-Lazy Amana Karya Najib el-Kailani - kartika, Sustry; Walidin, Muhammad (Kitabina: Jurnal Bahasa dan Sastra, 2024)
This research aims to explore the background of the novel ar-Rajul al-Lazy Amana from the perspective of a structural approach. This type of literature research is carried out by a descriptive method. The results of the research show that the setting in this novel shows the country of Italy, Qatar (Dubai), Italy (Rome), the Gulf, etc. While the Time Setting is a cycle of day and night. The background of happiness, sadness, doubt, and anger is the background of the atmosphere captured in this novel. The harmony of the setting provides a clear picture so that it brings the novel to life as a whole.